1995
DOI: 10.1042/bj3120511
|View full text |Cite
|
Sign up to set email alerts
|

Protease-susceptible sites and properties of fragments of aortic smooth-muscle myosin

Abstract: We have examined the protease susceptibility of aortic myosin, the thermal unfolding profiles of myosin rod and light meromyosin (LMM) and the solubility properties of the LMM fragments. Two major protease-susceptible sites were found, located at the head-rod junction and the heavy meromyosin (HMM)-LMM junction. Both tryptic and chymotryptic digestion of aortic myosin rod produced the LMM (80-85 kDa) and short subfragment 2 (S-2) (40-45 kDa) segments, which were similar to those of gizzard myosin rod and diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…This information, together with the finding that peptides between 40 and 30 kDa had different concentrations in cysticerci and tapeworms, points to differences in amino acid sequences and therefore suggests that they correspond to isoforms. We can also suggest that digestion performed in the gel was a successful procedure since similar peptides to those described in previous reports were found (King et al, 1995;Eddinger and Murphy, 1988;Tashiro et al, 1985). Furthermore, previous findings (King et al 1995) show that the flexible region in the tail of smooth muscle myosin is found in peptides that have molecular weights similar to those found in T. solium myosin (30e32 kDa).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This information, together with the finding that peptides between 40 and 30 kDa had different concentrations in cysticerci and tapeworms, points to differences in amino acid sequences and therefore suggests that they correspond to isoforms. We can also suggest that digestion performed in the gel was a successful procedure since similar peptides to those described in previous reports were found (King et al, 1995;Eddinger and Murphy, 1988;Tashiro et al, 1985). Furthermore, previous findings (King et al 1995) show that the flexible region in the tail of smooth muscle myosin is found in peptides that have molecular weights similar to those found in T. solium myosin (30e32 kDa).…”
Section: Discussionsupporting
confidence: 84%
“…The expression of myosin depends on the developmental stage, on the type and degree of contractile activity and tissue, therefore several myosin isoforms are found in the same organism (Arner et al, 2003;Berg et al, 2001;Babu et al, 2000). Myosin ATPase activities, limited proteolysis, electrophoretic separation and immunochemical assays are successful strategies for demonstrating the presence of isoforms (De la Cruz and Ostap, 2004;Blough et al, 1997;King et al, 1995;Kimura et al, 1991). Type II myosin and several actin isoforms were found in muscle fibers of Taenia solium Ambrosio et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The chymotrypsin subunit is at 0.9. related but different genes. The peptides common to all the digested MHCs probably correspond to conserved myosin regions, as described in previous reports (King et al, 1995;Eddinger and Murphy, 1988;Tashiro et al, 1985); the others are taeniid-specific. Our data show that metacestodes and adults of various taeniid parasites have different myosin II isoforms as judged by enzyme activity, V max , antigenic specificity and MHC peptide maps, as found previously for T. solium myosin and actin (Ambrosio et al, 1997Gonzalez-Malerva et al, 2004).…”
Section: Comparison Of Taeniid Mhc Peptide Mapssupporting
confidence: 72%
“…2). Interestingly, the antibody binding sites were nearly identical to the flexible regions of the rod that are predicted according to the amino acid sequence and electron microscopic observation (13,(35)(36)(37)(38)(39)(40), suggesting that the flexible regions have high antigenicity (Fig. 2).…”
Section: Binding Site Of Monoclonal Antibodies On Smooth Musclementioning
confidence: 94%